MARKET POLICY OF ALAUDDIN KHILJI: ANALYZING ECONOMIC STRATEGIES AND IMPLICATIONS IN MEDIEVAL INDIA - Bilal Ahmad Mugloo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Alauddin Khilji, the ruler of Medieval India, implemented market policies that aimed to strengthen the economy and consolidate his power. One significant policy was the establishment of a centralized market control system, including a state monopoly over key commodities. This allowed the government to regulate production, distribution, and pricing, ensuring a steady supply of essential goods and preventing hoarding. Price controls were also implemented to protect consumers and stabilize prices. Khilji established an intelligence network to monitor markets, detect illegal activities, and gather information. He promoted domestic trade, industries, and self-sufficiency to strengthen the economy. However, these policies had drawbacks, including a decline in economic activity, potential corruption, and limited growth opportunities for merchants. Khilji's market interventions were motivated by his desire to generate revenue for military campaigns, centralize power, and maintain social order. While they provided short-term stability, their long-term impact on economic growth and stability raises concerns. The sustainability of the centralized economic model and the restrictions on entrepreneurship and innovation are subjects of debate. Khilji's policies had implications for wealth distribution, social mobility, and the merchant class, concentrating power in the ruling elite and limiting opportunities for others. Comparisons with other rulers of the time, such as Sher Shah Suri and Akbar, highlight the diversity of economic governance approaches in Medieval India. Understanding Khilji's market policies contributes to our knowledge of the economic landscape of the time and its impact on society.